If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 1 = -2 + 8 Reorder the terms: 1 + y = -2 + 8 Combine like terms: -2 + 8 = 6 1 + y = 6 Solving 1 + y = 6 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + y = 6 + -1 Combine like terms: 1 + -1 = 0 0 + y = 6 + -1 y = 6 + -1 Combine like terms: 6 + -1 = 5 y = 5 Simplifying y = 5
| .2x+2=6 | | -4-8=-7+x | | -4y-10=6y+20 | | -4-8=-7 | | 19-42=3(x-2)-8 | | -2+9=14x-3-13x | | -5c+2=-18 | | -5(x+1)-11=21+3 | | 12(x-3)=-3-9 | | -2+5x=-32 | | 3x^3-9x^2+8x-7=2 | | 3(5y-4)=9y | | 6-x=20 | | -117=2(1-6p)-5p | | 5(5c-1)-4=21c+3 | | -(-9x-9y+4)= | | 3.5x=21 | | 4y^2-25x^2=100 | | 144=16t^2 | | 5=p+3 | | .3x+1.8=8 | | 3a-8a= | | 15x-2y=10 | | 5-.5x-3=4 | | 43y=6(7y-2) | | 6y=5(y+3) | | (x-3)(2x+3)=0 | | 5x^2=75 | | -2x-3-x=-3(-2x+7) | | 5x^2+25=100 | | 3(2x-3)=7 | | x^2+36=11 |